2018
DOI: 10.1007/s00127-018-1491-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation disparities in the co-occurrence of substance use and psychological distress: a national population-based study (2008–2015)

Abstract: PurposeAlthough strong evidence documents the elevated prevalence of both substance use and mental health problems among sexual minorities (i.e., gay, lesbian, and bisexuals), relatively less research has examined whether risk of the co-occurrence of these factors is elevated among sexual minorities compared to heterosexuals. The object of this study was to (1) explore sexual orientation-based differences in substance use, psychological distress, and their co-occurrence in a representative sample in Sweden, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
74
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 60 publications
8
74
1
3
Order By: Relevance
“…depression) than non‐SMs . Similar disparities in alcohol use and mental health issues have been observed in Europe , Canada and Australia .…”
Section: Introductionsupporting
confidence: 62%
“…depression) than non‐SMs . Similar disparities in alcohol use and mental health issues have been observed in Europe , Canada and Australia .…”
Section: Introductionsupporting
confidence: 62%
“…Tobacco‐related disparities for sexual and gender minorities are attributable to and impacted by multiple diverse, interrelated, and evolving factors such as the social determinants of health, tobacco industry influence, and the lack of comprehensive tobacco control policies . High rates of smoking by LGBT individuals have been linked, in part, to the stigma and discrimination associated with being a sexual or gender minority . Bränström and Pachankis’ research found that tobacco use cooccurred with psychological distress more often in LGB people than in their heterosexual counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…High rates of smoking by LGBT individuals have been linked, in part, to the stigma and discrimination associated with being a sexual or gender minority . Bränström and Pachankis’ research found that tobacco use cooccurred with psychological distress more often in LGB people than in their heterosexual counterparts. In another study, LGB and queer/questioning college students who reported frequent experiences of microaggressions in the last year were significantly more likely to report recent tobacco use .…”
Section: Introductionmentioning
confidence: 99%
“…Historically, lesbian, gay and bisexual (LGB) individuals have higher rates of smoking 4 , often attributed to targeted tobacco advertising 5,6 , exposure to stressors (i.e. minority status, stigma, homophobia, and gay bashing) 7,8 and psychological distress 9 . The same tendency of elevated ENDS use among LGB individuals has recently been documented 10 LGB groups are not homogeneous and differences may exist between tobacco use by men and women within the groups.…”
Section: Introductionmentioning
confidence: 99%